2021
DOI: 10.1007/s11249-021-01486-y
|View full text |Cite
|
Sign up to set email alerts
|

Bi2S3 and MoS2 Soft Coatings: A Comparative Study of Their Frictional Behavior Under Different Humidity Levels, Normal Loads, and Sliding Speeds

Abstract: Bi 2 S 3 is a promising solid lubricant for demanding applications, such as oil extraction, heavy mining, and aerospace components. However, so far its tribological behavior has not been studied in depth. Bi 2 S 3 soft coatings were evaluated utilizing reciprocating sliding tests under different levels of relative humidity level, contact stress, and sliding speed and the results were benchmarked against MoS 2 coatings. In addition, ab initio calculations using density functional theory modeling were employed f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…This explains the high COF values from the beginning of the tests, as the Bi 2 S 3 particles are being swept away by the steel ball. The adherence between Bi 2 S 3 and steel has been previously studied by Pilotti et al [19] using DFT modeling and it was found that it was significantly lower than the corresponding to MoS 2 .…”
Section: Wear Surface Characterizationmentioning
confidence: 93%
See 2 more Smart Citations
“…This explains the high COF values from the beginning of the tests, as the Bi 2 S 3 particles are being swept away by the steel ball. The adherence between Bi 2 S 3 and steel has been previously studied by Pilotti et al [19] using DFT modeling and it was found that it was significantly lower than the corresponding to MoS 2 .…”
Section: Wear Surface Characterizationmentioning
confidence: 93%
“…Additionally, the dispersion in the average COF values between the different test runs was also lower for the composite coatings when compared to neat MoS 2 ones. Several studies have reported that the frictional behavior of MoS 2 coatings becomes higher and more unstable as the humidity level increases [24,[29][30][31] According to Pilotti et al [19], the behavior exhibited by the composite coatings can be explained by the crystal structure of Bi 2 S 3 , as it could accommodate a higher amount of water molecules between the layers. By doing so, it prevents the compromise of the Pauli repulsion effect between the S atoms of the different MoS 2 layers caused by the presence of water molecules.…”
Section: Tribological Behavior In Humid Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The frictional behavior of burnished Bi 2 S 3 soft coatings was evaluated utilizing reciprocating sliding tests. 22 On the other hand, Bi 2 Se 3 retains a rhombohedral crystal structure of the space group D 3d (R3m). 18 The quintuple layers of Bi 2 Se 3 containing Se−Bi−Se−Bi−Se atoms bonded covalently are fastened together by weak van der Waals forces.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of bismuth sulfide as a powder lubricant was studied at temperatures up to 580 °C . The frictional behavior of burnished Bi 2 S 3 soft coatings was evaluated utilizing reciprocating sliding tests …”
Section: Introductionmentioning
confidence: 99%